(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to develop a drug information software solution for outpatients, allowing users to enter and look up personal prescriptions, as well as access drug and disease information alongside health communication resources. Research methods: The research involved building datasets for drug and disease information, establishing user requirement specifications (URS), designing user interfaces, and programming the drug information software for outpatients on a web-based platform. The software was then evaluated based on its functional performance. Results: A dataset that includes summary and detailed information for 427 drugs, along with infographic materials for over 50 common diseases, was successfully developed. URS were created based on functional modules, leading to the design of 19 user interfaces. The software, named Phasolpro DrugInfo, was programmed with capabilities such as storage, retrieval, and provision of information on prescriptions, drugs, and diseases; QR code generation and scanning for prescription data entry; health communication tools; and adverse drug reaction reporting. Patients can access these features through personal accounts. The software passed operational evaluations, showed good compatibility with various devices and browsers, and is now ready for practical implementation. Conclusion: The Phasolpro DrugInfo software meets the proposed requirements and supports the improvement of drug information services for outpatients.